2022
DOI: 10.1021/acsnano.2c06214
|View full text |Cite
|
Sign up to set email alerts
|

Strain Releasing of Flexible 2D Electronics through van der Waals Sliding Contact

Abstract: Two-dimensional (2D) materials have demonstrated promising potential for flexible electronics, owning to their atomic thin body thickness and dangling-bond-free surface. Here, we report a sliding contact device structure for efficient strain releasing. By fabricating a weakly coupled metal–2D junction with a van der Waals (vdW) gap in between, the applied strain could be effectively released through their interface sliding; hence minimized strain is transferred to the 2D lattice. Therefore, we observed stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…During the charging and discharging processes, the calculated diffusion coefficient ( D ) values of VO x /Mn–V 2 C are 9.98 × 10 −8 –1.02 × 10 −9 cm 2 s −1 , which is obviously greater than those of VO x /V 2 CT x (8.16 × 10 −9 –1.48 × 10 −10 cm 2 s −1 ). The D values of VO x /Mn–V 2 C are comparable to those of other reported materials used in aqueous ZIBs (Figure 4e and Table S2 (Supporting Information)), [ 11,15,25,42,44,61,68–70 ] which indicates that VO x /Mn–V 2 C possesses the rapid diffusion of zinc ions. The higher D values can be attributed to preintercalated Mn 2+ extending the interlayer spacing of the prepared Mn–V 2 C, which provide ordered channels for the rapid diffusion of Zn 2+ .…”
Section: Resultssupporting
confidence: 79%
“…During the charging and discharging processes, the calculated diffusion coefficient ( D ) values of VO x /Mn–V 2 C are 9.98 × 10 −8 –1.02 × 10 −9 cm 2 s −1 , which is obviously greater than those of VO x /V 2 CT x (8.16 × 10 −9 –1.48 × 10 −10 cm 2 s −1 ). The D values of VO x /Mn–V 2 C are comparable to those of other reported materials used in aqueous ZIBs (Figure 4e and Table S2 (Supporting Information)), [ 11,15,25,42,44,61,68–70 ] which indicates that VO x /Mn–V 2 C possesses the rapid diffusion of zinc ions. The higher D values can be attributed to preintercalated Mn 2+ extending the interlayer spacing of the prepared Mn–V 2 C, which provide ordered channels for the rapid diffusion of Zn 2+ .…”
Section: Resultssupporting
confidence: 79%
“…This is a significant increase over the evaporated‐contact device used as the control and the earlier results. [ 153 ] The geometry of the metal‐semiconductor sliding contact may also serve as motivation for the study of fundamental physics, such as piezo‐electronics, carrier transport, spin injection or exciton relaxation. Only simple circuits using no more than three discrete MoS 2 transistors have been built so far on flexible substrates due to material and fabrication process limitations.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…Li et al reported a strain-releasing vdW sliding metal contact for flexible electronics, as shown in Figure a. With evaporated Au in contact with the graphene layer on a polyimide (PI) substrate, a strong interaction between the evaporated metal and 2D graphene can induce cracks in the graphene by applying strain.…”
Section: Characterization and Applications Of Vdw Metal Contactmentioning
confidence: 99%
“…(a) Schematic of stretchable electronics integrated with the vdW metal contact. Reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: Characterization and Applications Of Vdw Metal Contactmentioning
confidence: 99%
See 1 more Smart Citation